Combustion characteristics, emissions and engine performances of a split injection diesel engine fueled with biodiesel blended fuels / Y.H. Teoh ...[et al.] - Y.H., Teoh; H.G., How; H.H., Masjuki; M.A., Kalam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Biodiesel can be fueled in compression ignition (CI) engine to substitute fossil diesel. However, the substitution of biodiesel in CI engine can increase the emissions of CO, NOx, HC and smoke. In the present study, the consequences of biodiesel addition, SOI timing and number of fuel injections on engine out responses of the diesel engine are investigated. Variation of the start of injection (SOI) timing and a number of fuel injections using 20% and 50% of biodiesel mixing ratios were carried out at a constant speed and load. The results showed that a significantly lower NOx level can be attained by retarding SOI timing for both of the biodiesel blended fuels and with a higher number of injection pulse. Interestingly, with B50 fuel operation, the concurrent decrement of NOx and smoke by an average of 12% and 37%, respectively, in comparison to the corresponding baseline diesel can be attained with late SOI and triple injection strategy. With optimum SOI timing setting, the splitting of fuel injection into multiple events can be used to address NOx-smoke trade-off in a CI engine in conjunction with the operation of biodiesel fuel.